Optimizing Nutrition and Complementary Care to Prevent Stunting - Dwikanthi, Rahayu; Jundra Darwanty; Warliana; Wiwin Fitriani; Cucu Santika; Sri Dinengsih; Vivi Silawati (International Journal of Community Services, 2025)
Stunting is a condition of failure to thrive in children. There are several things that are the main causes of the problem of stunting in children, one of which is the lack of public knowledge about stunting itself. The aim of implementing this Community Service is to increase public knowledge about stunting. The method for implementing PKM is lectures, discussions and questions and answers to the people of Cengkong Village, especially people who live in RT 01/RW 04. Evaluation of this activity is carried out by observing participants explaining about stunting and the practice of Lactation massage and Tuina massage. The evaluation results show that participants understand stunting and can do lactation massage and Tuina massage. It is hoped that public knowledge regarding stunting will be enhanced with Lactation massage and Tuina massage skills. reducing the risk of stunting problems, especially in Cengkong Village, Purwasari, Karawang.